ANALISIS PENERAPAN STANDAR PROSES DI SD NEGERI KALONGAN 03 - Adliroh, Adliroh; Wilarsati, Ari; Nurul Aprillia; Patto Prawansyah; Soedjono, Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning implementation plan (RPP) is a systematic plan so that the implementation of learning can run effectively and efficiently (Afandi, 2009). Apart from preparing lesson plans, teachers also assess student learning outcomes. Learning assessment is carried out during the learning process and at the end of the lesson. Assessments are carried out to measure the level of competency achievement of students, monitor the learning process, progress of learning outcomes, and improve the learning process (Mulyasa, 2010). This research aims to analyze how the educational process standards are implemented at Kalongan 03 State Elementary School. The research will be conducted by researchers using a qualitative approach. In general, the implementation of learning carried out by class teachers has followed the guidelines. The use of learning approaches is not yet diverse. There are still teachers who only use one learning approach and learning resources are not yet diverse. The learning aids that each school has are also different. Apart from that, it is also influenced by the level of creativity of the teachers.